2005
DOI: 10.1093/hmg/ddi048
|View full text |Cite
|
Sign up to set email alerts
|

CECR2, a protein involved in neurulation, forms a novel chromatin remodeling complex with SNF2L

Abstract: Chromatin remodeling complexes play critical roles in development. Here we describe a transcription factor, CECR2, which is involved in neurulation and chromatin remodeling. CECR2 shows complex alternative splicing, but all variants contain DDT and bromodomain motifs. A mutant mouse line was generated from an embryonic stem cell line containing a genetrap within Cecr2. Reporter gene expression demonstrated Cecr2 expression to be predominantly neural in the embryo. Mice homozygous for the Cecr2 genetrap-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
168
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 145 publications
(171 citation statements)
references
References 52 publications
2
168
0
1
Order By: Relevance
“…Both Cecr2 Gt45Bic and Cecr2 tm1.1Hemc homozygous mutants show defects in the orientation of the stereocilia bundles and the organization of the hair cell rows. In addition, we have previously shown that Cecr2 mutants have NTDs (exencephaly) and open eyelids (Banting et al, 2005). This combination of defects lead us to examine whether the PCP pathway was being affected by the loss of Cecr2.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Both Cecr2 Gt45Bic and Cecr2 tm1.1Hemc homozygous mutants show defects in the orientation of the stereocilia bundles and the organization of the hair cell rows. In addition, we have previously shown that Cecr2 mutants have NTDs (exencephaly) and open eyelids (Banting et al, 2005). This combination of defects lead us to examine whether the PCP pathway was being affected by the loss of Cecr2.…”
Section: Discussionmentioning
confidence: 99%
“…background (Banting et al, 2005). The collection of Cecr2 Gt45Bic embryos for inner ear analysis produced 1/73 exencephalic heterozygotes (1.3%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations